Beginner's guide to sketching : robots, vehicles and sci-fi concepts - Lewis, Marisa; Frye, John A.; Kuip, Guido (Worcester, United Kingdom : 3dtotal Publishing, 2019)
Following the success of Beginner's Guide to Sketching: Characters, Creatures and Concepts, 3dtotal Publishing presents readers with another fun, inspiring book on traditional sketching, with a focus on sci-fi themes. From robots and spaceships to buildings and aliens, Beginner's Guide to Sketching: Robots, Vehicles and Sci-fi Concepts is an informative starting point for any sci-fi-loving beginner artist who needs an introduction to traditional drawing and rendering techniques. Richly illustrated tutorials by industry professionals will guide the reader through learning a wide range of drawing tools, the basics of lighting and perspective, creating different rendering effects, and how to create sci-fi concepts that are both convincing and excitingly futuristic.
Table Of Contents: Introduction Getting Started John A. Frye Tools & materials Perspective basics Geometry, light & materials Concept design basics Projects Combat spaceship Lorin Wood Lunar roving buggy Milen Ivanov Prefab colony dwelling Rob Turpin All-terrain mining machine Guido Kuip Trading ship Lorin Wood High-tech luxury home Callie Wei Domestic helper robot Ang Chen Abandoned ship interior Qianjiao Ma Quick Studies Quadruped robot Dwayne Vance Breathing apparatus Jan Buragay Mysterious obelisk Wayne Haag Submersible craft Jeff Zugale Floating rock formation Riccardo Pagni Bipedalmech Dwayne Vance Control panel Erik Dillinger Hoverbike Jeff Zugale Mutant plant Riccardo Pagni Futuristic rifle Wayne Haag Specimen tank Erik Dillinger Advanced Projects Speeder vehicle scene: Using toned paper Jerel Dye Armed patrol robot: Digital sketching Michal Kus Contributors Glossary
Keywords: Drawing -- Technique; Robots in art; Automobiles in art; Fantasy in art